(untitled) (Journal of Current and Advance Medical Research, 2021)
Background: Nephron-sparing surgery is an accepted treatment modality for renal cell carcinoma (RCC) in certain situations. Objectives: The aim of this study was to compare perioperative outcomes after laparoscopic and open partial nephrectomy for patients with a solitary renal tumors of 7cm or less in different institutes in Dhaka. Methodology: Between June 2013 and October 2020, 23 patients had undergone LPN and 24 patients had undergone OPN for the treatment of solitary renal tumors of 7cm or less in different institutes in Dhaka. Large renal mass (>7cm), multiple tumor and patients with complex renal anatomy were excluded from this study. Patients having previous abdominal surgery were excluded from LPN and all LPN were performed transperitoneally. Results: Although the mean operative time was longer in the LPN than in the OPN group (134.4±35.36 (45-180) minutes versus 110.56±35.36 (60-165) minutes; P<0.001), the blood loss was comparable between the two groups (130 mL versus 180 mL; P value is not statistically significant). No blood transfusions were performed in either group. The hospital stay was significantly reduced after LPN compared with after OPN (2.8 days (2-6) versus 6.7 days (5-8); P <0.0002). 2 patients in LPN and 1 patient in OPN had positive surgical margins. Conclusion: This study has revealed that LPN is a feasible and safe alternative to the OPN with better surgical outcomes and similar oncological outcomes. Journal of Current and Advance Medical Research, January 2021;8(1):70-74